Pain Management during Bromelain-Based Enzymatic Debridement (NexoBrid®) in a USA Adult Burn Center - Martin R. Buta; Domenic Annand; Sarah Findeisen; Sean A. Hickey; Robert L. Sheridan; Jonathan S. Friedstat; John T. Schulz; Branko Bojovic; Edward A. Bittner; Jeremy Goverman (MDPI AG, 2023)
Outside the United States, bromelain-based enzymatic debridement (BBED) has become an effective tool for the removal of burn eschar. A primary concern with BBED is that it is a painful procedure requiring appropriate analgesia. The purpose of this study was to describe our experience using NexoBrid® (NXB), with a particular focus on pain management. We performed a retrospective review on all 32 adult burn patients enrolled at our institution as part of a multicenter phase 3 clinical trial (DETECT) or the expanded access treatment protocol (NEXT). All patients underwent BBED with NXB of acute deep partial- and full-thickness thermal burn wounds at a major burn center between November 2016 and February 2023. Thirty-two patients with an average age of 42.1 years (SD = 17.4, range 18-72) and an average TBSA of 6.3% (SD = 5.9, range 1-24.5) underwent a total of 33 BBED procedures. Only one patient required an additional NXB treatment, and all patients achieved >95% eschar removal. For pain control during debridement, seven patients required a local block (LB), nine a regional block (RB), and thirteen conscious sedation (CS). Three patients were intubated (INTB) for their burn injury prior to the procedure. There was no statistical difference in Numerical Pain Rating Scale (NPRS) scores during vs. before treatment or after vs. before treatment for all patients or when subdivided by BMI, race, TBSA, total area treated, and anesthetic type (LB, RB, and CS). With appropriate analgesia, the pain associated with BBED of acute deep partial- and full-thickness thermal burns is well tolerated.